Karakeristik Perilaku E-Transaksi Kalangan Mahasiswa - aryaningsih Ni Nyoman; IGA Oka Sudiadnyani; I Made Wirasyanti Dwi Pratiwi; Putu Rany Wedasuari (P3M Politeknik Negeri Bali, 2019)
The market share of e-commerce in Indonesia with the number of internet users grew by 30%. The value of e-commerce transactions is also very high, but the number of internet users for on-line shopping by 7%. Chinese people conduct on-line transactions. by 30%. The growth of e-commerce sales turnover of Asia Pacific region amounted to 42%. Transactions on-line smartphone users, e-mobile banking, e-digital use of other e-applications younger generation 25%. This study aims to examine the characteristics of the dimensions of e-transaction behavior among students and construct the dimensions of e-transaction behavior among students. The respondents of this research are among the 88 students and student who have been and are doing e-transactions of products and services. The data of this study were collected by questionnaire technique, in-depth interview and observation. The research data was analyzed by descriptive statistic and Factor analysis. The results of the research analysis indicate that the dimension of the formation of e-transaction behavior among students is determined by individual decisions, choices and psychology The recommendation of this research result can be formulated e-transactions policy to reduce the negative risk of market opportunity among the young generation.